Ergonomic Redesign of Farm Tools to Reduce Musculoskeletal Disorders among Nigerian Farmers - Hyginus Unegbu; D.S Yawasa (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The persistent prevalence of musculoskeletal disorders (MSDs) among Nigerian smallholder farmers remains a critical occupational health challenge, largely due to the prolonged use of poorly designed manual farm tools. This study investigated the ergonomic redesign of traditional hoes and cutlasses using a simulation-augmented, mixed-method experimental design aimed at reducing biomechanical stress and enhancing task efficiency. A total of 220 farmers (aged 18–65, with gender-balanced representation) from southwestern Nigeria participated in the study, ensuring population diversity and practical relevance. Redesign was guided by computer-aided design (CAD) modelling, finite element analysis (FEA), and field-collected anthropometric datasets. Key ergonomic indicators included Rapid Entire Body Assessment (REBA) for postural risk, surface electromyography (EMG) for muscle fatigue, task completion time, and the Borg Rating of Perceived Exertion (RPE) for perceived effort. Results showed statistically significant improvements (p < 0.01) across all performance metrics. REBA scores decreased from high to moderate/low risk categories, EMG activity reduced by over 30%, and task completion time improved by 33–36%. RPE scores were halved, indicating increased user comfort. Effect sizes (Cohen’s d > 1.2) confirmed the strong practical impact of the redesigned tools. While limited by short-term field exposure and a regional study scope, the research offers a replicable model for ergonomic tool development in informal agricultural systems. The findings support actionable interventions such as standardised tool design guidelines, local manufacturing protocols, and farmer training programmes. This study demonstrates that ergonomic simulation using CAD and biomechanical tools can lead to meaningful reductions in MSD risk, improved task performance, and higher usability in resource-limited farming environments.